Randomized clinical trials in obstetrics-gynecology registered at ClinicalTrials.gov: Characteristics and factors associated with publication. (August 2020) - Gupta, Megha; Petsalis, Marina; Powers, Katherine; Chen, Han-Yang; Chauhan, Suneet P.; Wagner, Stephen
Abstract: Objective: To describe the characteristics of obstetrical and gynecological randomized clinical trials (RCTs) that were registered at a national database, and to identify factors associated with the publication among the completed trials. Study Design: This was a cross-sectional study using data from ClinicalTrials.gov which was queried for all obstetrical and gynecological RCTs that were registered between January 1, 2009 and December 31, 2013. Poisson regression models were used to examine the factors associated with publication among the completed trials (using relative risk [RR] and 95 % confidence interval [CI]). Results: During the 5-year study period, 1389 obstetrical and gynecological RCTs were registered at ClinicalTrials.gov: 31 % (n = 538) in obstetrics and 69 % (n = 851) in gynecology. Among all registered RCTs in obstetrics-gynecology, 59 % (n = 816) were completed and 29 % (n = 406) were published. Compared to registered trials that were unpublished, those that were published were more likely to be funded by NIH/US Federal Government (RR = 3.36, 95 % CI = 1.46−7.74) or other non-industry organizations (RR = 2.41, 95 % CI = 1.07−5.38), have a procedural intervention (RR = 1.52, 95 % CI = 1.12−2.06), or an enrollment of >150 (RR = 2.73, 95 % CI = 1.57−4.75). Conclusion: Among the obstetrical and gynecological randomized controlled trials registered at ClinicalTrials.gov, less than two-third were completed, and only one-third were published.